The coronavirus pandemic: exploring expectant fathers' experiences. Issue 1 (2nd January 2022) - Menzel, Alice
ABSTRACT: The Coronavirus pandemic raises significant concerns about pervasive social inequities and disparate gender relations, particularly between mothers/fathers. Indeed, the pandemic engendered a general retreat into traditional parenting roles across myriad, everyday, institutional, spaces, including workplaces, homes, and welfare/healthcare services. These effects have been especially marked for couples expecting a child. Visitor-restriction policies, implemented to curb viral-spread within healthcare settings, effectively 'barred' many expectant fathers in the UK (and elsewhere) from attending antenatal appointments, and even the birth of their child; milestone moments widely regarded as significant socio-cultural 'rites-of-passage' in fathers' transition to parenthood. Many pregnant women had to face these moments alone, sparking campaigns including #ButNotMaternity. This paper critically examines how such institutional responses exhibit a complex 'welfare trade-off' effectively (re)positioning fathers as spectators, rather than participants, in pregnancy/parenthood and risk embodying a potential U-turn to recent decades' emphasis on involved, equitable fatherhood. Drawing upon the accounts of expectant mothers/fathers in the UK reported in the popular press since March 2020 and the #ButNotMaternity campaign, it employs thematic social-media analysis to explore the emotional impacts of visitor-restrictions and the gendered, emotional governance of parenting amidst the pandemic through the exclusion of particular (fathers') bodies within maternity care spaces.